NUTRITIONAL INTERVENTIONS AND SUPPLEMENTATION AS SUPPORTIVE THERAPY FOR ENDOMETRIOSIS: A SYSTEMATIC REVIEW - Sylwia Nycz-Jucha; Idalia Myszor; Brygida Pinkowicz; Paulina Łobaza; Michał Madej; Maria Kubacka; Lucjan Kocemba; Gabriela Mroczka; Piotr Rachwał; Barbara Nowak-Misiąg (International Journal of Innovative Technologies in Social Science, 2026)
Endometriosis is a chronic disease characterised by the presence of endometrial tissue outside the uterine cavity. It is associated with pain, menstrual disorders, and infertility. Despite advances in research, its aetiology remains incompletely understood; however, genetic, hormonal and immunological factors and microbiome disorders are believed to contribute to its development. Diagnosis of the disease is frequently delayed, and laparoscopy remains the gold standard for confirmation. Current treatment options include hormonal pharmacotherapy, most commonly oral contraceptives and progestogens such as dienogest, and surgical intervention, which is associated with a risk of recurrence and postoperative complications. An increasing body of evidence highlights the role of nutritional interventions and supplementation in modulating inflammatory processes, oxidative stress, angiogenesis and estrogen metabolism. Nutrients and bioactive compounds such as omega - 3 fatty acids, vitamins D, C and E, phytoestrogens, resveratrol, curcumin and melatonin may reduce the severity of symptoms and the size of ectopic endometrial lesions. The microbiome also plays an important role - probiotics, short-chain fatty acids and faecal microbiota transplantation demonstrate therapeutic potential through modulation of the immune response and estrogen metabolism. A multidirectional approach integrating pharmacotherapy, surgical treatment, and lifestyle modification may improve patients’ quality of life; however, further research is required to evaluate the efficacy and safety of adjuvant therapies.